Tipo-morfologi Kawasan dan Permukiman Desa Oro-oro Ombo Kota Batu - Wijaya, Budi Tri (University of Merdeka Malang, 2017)
The Batu City of tourism city, will develop and growing with the advent of time and on the change.The development tourist object continous increased, causing the quality of global environment.Oro-oro ombo village located in Batu city tourism. We have caused the changes tourism in the areaof the village. The purpose of examining the case is to know how to build a place that is a factor thatinfluences the change. The study case used the tipology- morfology approach. Data collectionmethod of literature data direct observation. To know physical characters the region and nonphysical. Data analysis methods using method descriptive analysis to describe the condition ofbeing perceived respondent about variables that set a model research. The change of Oro-oro ombovillage because of the influence of tourist activities start since 2008 raises the occurrence of changein good physical condition or non-physical. The physical aspect residential compound Oro-oroombo village can be seen the context of the scale of macro and micro. On aspect of non-physical,social culture and socil economy community affecting the settlement pattern.Â DOI: https://doi.org/10.26905/lw.v9i1.1866